Experimental investigation of electron heating modes in capacitively coupled radio-frequency oxygen discharge. (12th November 2019) - Babu, S K; Kelly, S; Kechkar, S; Swift, P; Daniels, S; Turner, M M
Abstract: A Langmuir probe has been used to investigate electron heating mechanisms in a capacitively coupled oxygen discharge over a wide pressure range (50–800 mTorr) at a fixed applied power (200 W). Evidence presented here from experimentally obtained electron energy distribution functions (EEDFs) illustrates discharge transition from a collisionless (stochastic) to a collisional (Ohmic) dominant regime with increasing oxygen pressure. The discharge exhibited a bi-Maxwellian EEDF in the collisionless regime, dominated by stochastic heating whereas Druyvesteyn-like EEDFs were exhibited in the collisional dominant regime. Moreover, in the transition between these two regimes, parameters such as electron density, effective electron temperature and electron-neutral collision frequency exhibited significant variations.